Evolution of Language and of Writing Media in Ancient Yellow-Yangtze River Civillization - Waishol, Yusuf; Ningrum, Setia; Sucahyo, Iqbal Rizki; Kirana, Ai (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
During the Shang Dynasty, rebus or divination artifacts appeared on bones, which is the earliest medium for writing Chinese characters. Based on the discovery of boiled artifacts as a medium for writing Chinese characters, we can know that during the Shang Dynasty (1064-1600 BC) there was a language system and a reading and writing system used in a wide area, and the Yangtze River and Yellow River were important factors that supported deployment of the system. The existence of this language system and reading and writing system can mean that this area has developed to the stage of advanced civilization. The research method used is the historiography (history) method. Research begins with selecting a subject or topic which takes place through four main steps, namely, heuristics (searching for sources), criticism (selecting and sorting reliable and valid sources), interpretation (interpretation or meaning) and historiography (writing history). The results of this research are the development and standardization of language that occurred in the Yellow-Yangtze River civilization which includes writing media, vocabulary sounds (phonemes), influenced by social, religious and political factors.